2018
DOI: 10.1002/ente.201800274
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Diamine Cross‐Linker on Semi‐IPNs of BPPO/SPEEK Membranes for Direct Methanol Fuel Cell

Abstract: Low methanol permeability is one of the most critical factors for proton exchange membranes utilized in direct methanol fuel cells (DMFCs). Here, sulfonated poly(ether ether ketone) (SPEEK) polymer chains are interpenetrated into the semi‐interpenetrating polymer networks (semi‐IPNs) constructed by the alkylation reaction between bromobenzyl groups of bromomethylated poly(phenylene oxide) and amine groups of 2,2′‐(ethylenedioxy)bis(ethylamine) cross‐linker. The influences of crosslinking network contents on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Increasing the mobility of water molecules and polymer chains at high temperatures increases the vacant spaces for proton transfer in the membrane. 52 Also, increasing the proton mobility at high temperatures has an influence on proton jumping from SO 3 − H 3 O + (Grotthuss mechanism). The results show that the PEM with 5 wt % SO 3 H−TiO 2 @TDI@EN-SO 3 H loading achieved the best proton conductivity at different temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the mobility of water molecules and polymer chains at high temperatures increases the vacant spaces for proton transfer in the membrane. 52 Also, increasing the proton mobility at high temperatures has an influence on proton jumping from SO 3 − H 3 O + (Grotthuss mechanism). The results show that the PEM with 5 wt % SO 3 H−TiO 2 @TDI@EN-SO 3 H loading achieved the best proton conductivity at different temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…According to Arrhenius plots shown in Figure , the as-prepared PEMs exhibited an upward trend of the proton conductivity with the temperature. Increasing the mobility of water molecules and polymer chains at high temperatures increases the vacant spaces for proton transfer in the membrane . Also, increasing the proton mobility at high temperatures has an influence on proton jumping from SO 3 – H 3 O + (Grotthuss mechanism).…”
Section: Resultsmentioning
confidence: 99%
“…Fuel cells are clean and highly efficient energy conversion devices because they can directly convert the chemical energy of fuels (hydrogen, methanol, and ethanol etc.) to electrical energy. Among fuel cells, the direct methanol fuel cell (DMFC) has attracted extensive attention because of the high specific energy density of methanol, plentiful methanol sources, and simplified system construction. As one of the key components of DMFCs, the proton exchange membrane (PEM) is responsible for transferring protons and preventing fuels permeating between the two electrodes during the DMFC operation process. The commercially used Nafion membranes possess many outstanding advantages, like high proton conductivity, outstanding mechanical strength, and excellent chemical and dimensional stability. However, the serious methanol permeation of Nafion membranes limits them to applications only in DMFCs fed with low concentration methanol solutions, almost lower than 5 M, which results in at least 4 times lower power output than the DMFCs offered by neat methanol (24.8 M). The most effective way to develop high concentration DMFCs is to replace Nafion membranes by novel high methanol-permeation resistant PEMs. In the past several decades, several alternatives such as sulfonated polyimide (SPI), , sulfonated polyamide (SPA), sulfonated poly­(arylene ether) (SPAE), and sulfonated poly­(ether ether ketone) (SPEEK) , have been widely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] The structural parameters include the physical parameters of the membrane electrode assembly (MEA) and the geometric parameters of the flow field structure. [11][12][13] Studies showed that optimizing the operating parameters and the cell structure are two effective ways to enhance DMFC performance. [14][15][16][17] Yang et al [18] developed a serpent flow fields structure for DMFC, and the results showed that with this structure, the DMFCs delivered better performance under various conditions.…”
mentioning
confidence: 99%